Pemanfaatan Media Flashcard Melalui Belajar Kelompok pada Mata Pelajaran Ekonomi Syariah - Fitri Kurnia (Tarbawi : Jurnal Studi Pendidikan Islami, 2023)
A study conducted on SMK Bayt Al- Hikmah Pasuruan's 10th grade students found that the majority of the teaching strategies employed in Islamic Religious Education (PAI) classes were lecture-based, which resulted in a lack of variety in the approaches used. This resulted from the PAI teachers' lack of experience with teaching techniques and their foreign graduation backgrounds.Furthermore, education specialist Mr. Munif Chatib's "Sekolahnya Manusia" (School of Humanity) methodology was implemented in SMK Bayt Al-Hikmah. This method divides intelligence in pupils into eight categories. Many SMK Bayt Al-Hikmah 10th graders showed visual intelligence and preferred a hands on approach to learning, however the current teaching strategies did not suit their learning preferences. As a result, a sizable portion of pupils had scores lower than the passing mark (KKM) of 75. To tackle this problem, the researcher tried to make things better by employing flashcards as a teaching aid in PAI classes, with a particular emphasis on Islamic economics. The researcher and subject teachers collaborated as part of the Classroom Action Research approach used in this study. Six male and eight female students in the tenth grade at SMK Bayt Al-Hikmah Pasuruan participated in the study. Two rounds of planning, implementation, observation, and reflection comprised each cycle of the research. Utilizing tools including instructor activity sheets, student activity sheets, test sheets, and questionnaires, data collecting procedures included observations, tests, and questionnaires. Based on test results, questionnaire replies, and observations of both teachers and students, quantitative data analysis was carried out. From 77% in the first cycle to 87.5% in the second, there was an increase in teacher activity. Additionally, from 71.42% in the first cycle to 92.8% in the second, student activity rose. Additionally, pupils' conceptual knowledge increased, rising from 70% in the first cycle to 87% in the second. To sum up, the implementation of flashcards improved learning outcomes for SMK Bayt Al-Hikmah Pasuruan's 10th-grade students by enhancing teacher and student activities during the learning process.